Performance analysis of a latent heat storage system with phase change material for new designed solar collectors in greenhouse heating - Benli, Hueseyin; Durmus, Aydin (Pergamon-Elsevier Science Ltd, 2009)
The continuous increase in the level of greenhouse gas emissions and the rise in fuel prices are the main driving forces behind the efforts for more effectively utilize various sources of renewable energy. In many parts of the world, direct solar radiation is considered to be one of the most prospective sources of energy. In this study, the thermal performance of a phase change thermal storage unit is analyzed and discussed. The storage unit is a component of ten pieced solar air collectors heating system being developed for space heating of a greenhouse and charging of PCM. CaCl(2)6H(2)O was used as PCM in thermal energy storage with a melting temperature of 29 degrees C. Hot air delivered by ten pieced solar air collector is passed through the PCM to charge the storage unit. The stored heat is utilized to heat ambient air before being admitted to a greenhouse. This study is based on experimental results of the PCM employed to analyze the transient thermal behavior of the storage unit during the charge and discharge periods. The proposed size of collectors integrated PCM provided about 18-23% of total daily thermal energy requirements of the greenhouse for 3-4 h, in comparison with the conventional heating device. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Solar air collector (SAC); Thermal energy storage (TES); Latent heat storage (LHS); Phase change material (PCM); Greenhouse